Harmonisation in study design and outcomes in paediatric antibiotic clinical trials: a systematic review. Issue 9 (September 2016) - Folgori, Laura; Bielicki, Julia; Ruiz, Beatriz; Turner, Mark A; Bradley, John S; Benjamin, Daniel K; Zaoutis, Theoklis E; Lutsar, Irja; Giaquinto, Carlo; Rossi, Paolo; Sharland, Mike
Summary: There is no global consensus on the conduct of clinical trials in children and neonates with complicated clinical infection syndromes. No comprehensive regulatory guidance exists for the design of antibiotic clinical trials in neonates and children. We did a systematic review of antibiotic clinical trials in complicated clinical infection syndromes (including bloodstream infections and community-acquired pneumonia) in children and neonates (0–18 years) to assess whether standardised European Medicines Agency (EMA) and US Food and Drug Administration (FDA) guidance for adults was used in paediatrics, and whether paediatric clinical trials applied consistent definitions for eligibility and outcomes. We searched MEDLINE, Cochrane CENTRAL databases, andClinicalTrials.gov between Jan 1, 2000, and Nov 18, 2015. 82 individual studies met our inclusion criteria. The published studies reported on an average of 66% of CONSORT items. Study design, inclusion and exclusion criteria, and endpoints varied substantially across included studies. The comparison between paediatric clinical trials and adult EMA and FDA guidance highlighted that regulatory definitions are only variably applicable and used at present. Absence of consensus for paediatric antibiotic clinical trials is a major barrier to harmonisation in research and translation into clinical practice. To improve comparison of therapies and strategies, international collaboration among all relevant stakeholders leading to harmonised case definitions and outcome measures is needed.